2007
DOI: 10.1111/j.1365-2672.2007.03442.x
|View full text |Cite
|
Sign up to set email alerts
|

The application of chromogenic media in clinical microbiology

Abstract: Summary Since 1990, a wide range of chromogenic culture media has been made commercially available providing useful tools for diagnostic clinical microbiology. By the inclusion of chromogenic enzyme substrates targeting microbial enzymes, such media are able to target pathogens with high specificity. Examples of target pathogens include Staphylococcus aureus, Streptococcus agalactiae, Salmonella spp. and Candida spp. The inclusion of multiple chromogenic substrates into culture media facilitates the differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 73 publications
0
82
0
3
Order By: Relevance
“…According to the studies by Salvatore et al, (2011), Parveen et al, and Sharmin et al, (2010), only 40-50% showed significant bacterial growth (Salvatore et al, 2011;Parveen et al, 2011;Sharmin et al, 2010). A higher rate of isolation was reported from a study in UK (54.2% single growth and 21.6% mixed growth) by Perry and Freydiere, (2007).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…According to the studies by Salvatore et al, (2011), Parveen et al, and Sharmin et al, (2010), only 40-50% showed significant bacterial growth (Salvatore et al, 2011;Parveen et al, 2011;Sharmin et al, 2010). A higher rate of isolation was reported from a study in UK (54.2% single growth and 21.6% mixed growth) by Perry and Freydiere, (2007).…”
Section: Resultsmentioning
confidence: 74%
“…According to the studies by Salvatore et al, (2011), Parveen et al, (2011) 51 andSharmin et al, (2010) predominant growth was Escherichia coli (Salvatore et al, 2011;Parveen et al, 2011;Sharmin et al, 2010 Lakshmi et al, (2004) and Perry and Freydiere (2007) suggested that best advantage of chromogenic media over other media was easy recognition of mixed growth and preventing the need for subculturing and performing multiple biochemical tests (Perry et al, 2007). Cystein Lactose Electrolyte Deficient Agar with Andrade's indicator showed colour changes depending on the production of acid by different organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Such metabolic enzyme substrates are commonly used in selective growth medium for the isolation of bacteria [17][18][19]. However, the liberated label compound will contain either a chromophore or fluorophore, which will result in the formation of coloured/fluorescent colonies upon growth of the target bacteria; the colour/fluorescence pertaining to the presence of a specific enzyme produced by the target microorganism.…”
Section: Use Of Enzyme Substrates To Liberate Exogenous Vocsmentioning
confidence: 99%
“…e.g. SMID agar (BioNerieux, France), Rainbow Salmonella agar (Biolog, USA), CHROMagar Salmonella (CHROM agar, France), chromogenic Salmonella esterase agar (PPR Diagnostics Ltd, UK), Compass Salmonella agar (Biokar diagnostics, France), and chromogenic ABC medium (Lab M. Ltd., UK) (Maciorowski et al, 2006;Manafi, 2000;Perry et al, 2007;Schonenbrucher et al, 2008) Read the colour of the butt and of the surface of the medium; ALK: A red colour corresponding to no acid production; NC: No change in the colour of the medium ; A: A yellow colour corresponding to acid production; G: Gas production in the butt; H 2 S production; +: Black colour; -: No black colour…”
Section: Nonmentioning
confidence: 99%